The Role of Calcium in the Desensitization of Capsaicin Responses in Rat Dorsal Root Ganglion Neurons - Koplas, Patricia A. (J Neurosci, 1997)
Capsaicin (Cap) is a pungent extract of theCapsicum pepper family, which activates nociceptive primary sensory neurons. Inward current and membrane potential responses of cultured neonatal rat dorsal root ganglion neurons to capsaicin were examined using whole-cell and perforated patch recording methods. The responses exhibited strong desensitization operationally classified as acute (diminished response during constant Cap exposure) and tachyphylaxis (diminished response to successive applications of Cap). Both acute desensitization and tachyphylaxis were greatly diminished by reductions in external Ca(2+) concentration. Furthermore, chelation of intracellular Ca(2+) by addition of either EGTA or bis(2-aminophenoxy)ethane-N,N,N′,N′-tetra-acetic acid to the patch pipette attenuated both forms of desensitization even in normal Ca(2+). Release of intracellular Ca(2+) by caffeine triggered acute desensitization in the absence of extracellular Ca(2+), and barium was found to effectively substitute for calcium in supporting desensitization. Cap activated inward current at an ED(50) of 728 nm, exhibiting cooperativity (Hill coefficient, 2.2); however, both forms of desensitization were only weakly dependent on [Cap], suggesting a dissociation between activation of Cap-sensitive channels and desensitization. Removal of ATP and GTP from the intracellular solutions resulted in nearly complete tachyphylaxis even with intracellular Ca(2+) buffered to low levels, whereas changes in nucleotide levels did not significantly alter the acute form of desensitization. These data suggest a key role for intracellular Ca(2+) in desensitization of Cap responses, perhaps through Ca(2+)-dependent dephosphorylation at a locus that normally sustains Cap responsiveness via ATP-dependent phosphorylation. It also seems that the signaling mechanisms underlying the two forms of desensitization are not identical in detail.